2017
DOI: 10.1016/j.atmosres.2017.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal dimension of lightning flashes based on three-dimensional Lightning Mapping Array

Abstract: ABSTRACT3D mapping system like the LMA -Lightning Mapping Array -are a leap forward in lightning observation. LMA measurements has lead to an improvement on the analysis of the fine structure of lightning, allowing to characterize the duration and maximum extension of the cloud fraction of a lightning flash. During several years of operation, the first LMA deployed in Europe has been providing a large amount of data which now allows a statistical approach to compute the full duration and horizontal extension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…The flash size in winter thunderstorms seemed to be larger than in summer thunderstorms. In the studies mentioned above, López et al () obtained mean and median flash lengths in summer thunderstorms of 15.0 and 10.3 km, respectively. Yoshida et al () suggested that the median area of the convex hull of summer flashes around the Japanese Kanto region was approximately 26 km 2 (counted based on the given square root value).…”
Section: Summary and Discussionmentioning
confidence: 96%
“…The flash size in winter thunderstorms seemed to be larger than in summer thunderstorms. In the studies mentioned above, López et al () obtained mean and median flash lengths in summer thunderstorms of 15.0 and 10.3 km, respectively. Yoshida et al () suggested that the median area of the convex hull of summer flashes around the Japanese Kanto region was approximately 26 km 2 (counted based on the given square root value).…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Median values of the flash size parameters were 0.27 s for duration, 5.54 km for horizontal distance, 3.67 km for vertical distance, 9.67 km 2 for flash area, and 14.37 km 3 for flash volume, as shown in Table . For comparison, Brook and Kitagawa () documented a median flash duration of 0.5 s using the definition that the duration was the time interval between the first burst of pulse activity and the last detectable R‐ or K‐change pulse, and López et al () reported median (mean) flash durations of 0.35 (0.44) s in summer storms and 0.41 (0.45) s in winter storms with LMA flashes containing more than 50 sources. These values are larger than those found in this study.…”
Section: Statistics For Flash Size Propertiesmentioning
confidence: 99%
“…Flash size properties have attracted interest in recent years and typically comprise measures of spatial extension and maintenance that include flash duration, channel length, horizontal extent, and flash area, based on the observations of 3‐D lightning location systems or satellite‐based lightning imaging equipment (Beirle et al, ; Bruning & MacGorman, ; Lang et al, ; López et al, ; Peterson, Deierling, et al, ; Peterson & Liu, ; Peterson, Rudlosky, et al, ; Thomas et al, ; Zhang et al, ; Zhang et al, ; Zheng & MacGorman, ). Lang et al () reported the world's largest flash with a horizontal distance of 321 km measured on 20 June 2007 across parts of Oklahoma and the world's longest flash with a duration of 7.74 s measured on 30 August 2012 over parts of southern France.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the winter and summer flash length distributions in Spain has been performed by López et al . . They examined 3D location data estimated by the Ebro LMA in Spain and showed the flash length distributions for both winter (December–February) and summer (June–August).…”
Section: Statistical Comparison Of Winter Lightning To Summer Lightnimentioning
confidence: 99%